2016
DOI: 10.21276/ijirem.2016.3.6.5
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Different ANN Based Fault Detection Techniques for HVDC Systems

Abstract: Neural Network has been one among few best choices for the detection of faults in electrical systems. HVDC transmission system has no doubt first choice for the long transmission of electricity all over the world. This paper presents a use of different artificial neural network for the fault detection & classification in HVDC transmission system. Here an attempt is made to cite the scholarly work done and available on renounced journals with excellent review on their work. The work is valuable and may be light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Typically, in a power system, the values of voltage and current are very unstable and change under various types of faults. Hence, an artificial neural network would be a great choice for detecting, classifying, and locating the transmission line faults of HVDC systems, as a neural network is basically able to incorporate dynamic changes in power systems [28][29][30][31][32].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Typically, in a power system, the values of voltage and current are very unstable and change under various types of faults. Hence, an artificial neural network would be a great choice for detecting, classifying, and locating the transmission line faults of HVDC systems, as a neural network is basically able to incorporate dynamic changes in power systems [28][29][30][31][32].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Other researchers demonstrated that the fault detection and classification algorithm is based on a modified Clarke's transformation, while a model based on artificial neural networks (ANNs) improves fault detection and classification [20]. The effectiveness of ANN applications for fault detection on HVDC transmission lines is compared, and neural network-based fault detection techniques are presented by Nagar and Shah [21].…”
Section: -Hvdc Transmission Systemmentioning
confidence: 99%
“…Artificial neural networks (ANN) or connectionist systems are computing systems based on biological neural networks that make up animal brains [25]. Neural network has been viewed as framework rather than been called an algorithm, which enhances several differ machine learning algorithms not only to work together but also process complex inputs data [26], [27].…”
Section: Ann-based Fault Analysismentioning
confidence: 99%